Eat, Learn, Remember - Seda Artis, Aise; Seda Artis, Aise (IntechOpen, 2019)
Memory is mainly the outcome of learning. And forgetting is sometimes a blessed physiological event, and sometimes part of a serious pathology. Recent findings suggest that alterations in the gut microbiome may play a pathophysiological role in human brain diseases. It has been a challenge for neuroscientists to understand the basic processes of memory storage in both health and disease conditions. Our ability to store and process what is going on and use the classified information basically relies on memory being a constructive, fallible process. Here you will find a tiny reflection of the accumulated knowledge for scientific practice. In your daily life do not forget to eat to live, live to learn, and remember to value everything just as much as you deserve.
English
Keywords: Cognition & cognitive psychology; Cognition & cognitive psychology